The Effect of Product Quality, Product Price, Electronic Word of Mouth, and Brand Image on Purchase Decisions - Stevie Stevie; Rodhiah Rodhiah (International Journal of Management Science and Application, 2025)
In a highly competitive automotive market like Jakarta, consumer purchasing decisions are influenced by various factors, including product quality, price, electronic word of mouth (e-WOM), and brand image. However, previous research has focused more on everyday consumer products, while studies on high-value products like motorcycles are still limited. This research aims to analyze the influence of product quality, price, e-WOM, and brand image on decisions to purchase Honda motorcycles in Jakarta. The research method used is a quantitative approach with a purposive sampling technique applied to 120 respondents. Data were analyzed using Partial Least Squares (SmartPLS)-based Structural Equation Modeling (SEM). The research results indicate that product quality, price, and e-WOM do not significantly influence purchase decisions, while brand image has a positive and significant effect. This finding confirms that brand image is a dominant factor in driving consumer purchasing decisions for automotive products. The implication of this research is the need for a marketing strategy that focuses on strengthening brand image through consistent brand communication, improved after-sales service, and product innovation to reinforce consumer perception.